2016
DOI: 10.1038/srep22366
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PANDAR regulates the G1/S transition of breast cancer cells by suppressing p16INK4A expression

Abstract: It has been reported that lncRNA PANDAR (promoter of CDKN1A antisense DNA damage-activated RNA) is induced as a result of DNA damage, and it regulates the reparation of DNA damage. In this study, we investigated the role of lncRNA PANDAR in the progression of breast cancer and found that PANDAR was up-regulated in breast cancer tissues and cell lines. The knockdown of PANDAR suppresses G1/S transition of breast cancer cells. We demonstrated mechanistically that the regulation of G1/S transition by PANDAR was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 41 publications
2
60
1
1
Order By: Relevance
“…A recent study indicated that PANDAR acts as a tumor-promoter in breast cancer by regulating G1/S transition. PANDAR-mediated promotion of cell proliferation occurs via regulation of p16 INK4A 28. In order to understand the biological functions of PANDAR in CCA, we examined the differences in cell proliferation after suppressing PANDAR expression by using CCK-8 and colony formation assays.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that PANDAR acts as a tumor-promoter in breast cancer by regulating G1/S transition. PANDAR-mediated promotion of cell proliferation occurs via regulation of p16 INK4A 28. In order to understand the biological functions of PANDAR in CCA, we examined the differences in cell proliferation after suppressing PANDAR expression by using CCK-8 and colony formation assays.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that various transcription factors, such as Ets and Bmi1, play critical roles in the transcriptional regulation p16 gene5. Our earlier studies showed that the histone acetyltransferase p300 recruited by Sp1 stimulated p16 transcription through inducing the H4 hyperacetylation on p16 gene, whereas HDAC3/4 inhibited the p16 promoter activity via the transcription factors YY1 and ZBP-89678.…”
mentioning
confidence: 95%
“…It is induced during DNA damage in a p53-dependent manner and inhibits the expression of apoptotic genes [19]. Aberrant PANDAR expression is reported in a variety of human cancers, including bladder cancer, breast cancer, osteosarcoma etc [20][21][22][23]. It exerts numerous molecular functions, such as promoting cell proliferation, invasion, epithelial-mesenchymal transition and metastasis, besides, it can suppress tumor cell apoptosis [20][21][22][23][24][25].…”
Section: Meta-analysismentioning
confidence: 99%